PENINGKATAN KUALITAS SUMBER DAYA MANUSIA MELALUI PROGRAM PELATIHAN DI DESA TANGKUP KARANGASEM MENUJU DESA WISATA RINTISAN - Putu Agus Prayogi; Komang Krishna Yogantara (Universitas Triatma Mulya, 2022)
The socialization and training activities carried out in the implementation of the Community Service Program at the Faculty of Business and Tourism, Triatma Mulya University in Tangkup Village, Sidemen Karangasem District, provide opportunities for students and lecturers to carry out community service activities in the form of mentoring and training activities. The students are trained to be able to interact with the community and be able to apply the knowledge they gain, so that they gain experience from this activity. Mental and personality formation is also the goal of organizing this community service activity. As for the lecturers, this activity is a form of implementing the Tri Dharma of Higher Education, especially in research and community service activities. The accompanying lecturers will obtain a lot of information related to the problems faced by the community, so that in this activity it is expected that the lecturers can provide solutions related to the problems faced by the community. This community service program resulted in findings that Tangkup Village has the potential to develop a homestay by utilizing residents' houses. From the results of the observation, it can be seen that there are several residential houses that are feasible to be developed into homestays. For this reason, homestay management training will have a good impact on the development of accommodation facilities in Tangkup Village, as a form of preparing Tangkup Village as a Pilot Tourism Village.